Early breast cancer detection by using a sensor-antenna (2020)
In the last decades, the early detection of cancer has motivated many researches works because these increases the possibilities of survival of patients and positive responses to different treatments. Particularly, this work concerns the preliminary results obtained in the detection of a cancerous tumor (5 mm cube) at early stage that concerns a breast using a sensor-antenna. The sensor-antenna operates at a frequency of 2.45 GHz. A breast model was implemented in ANSYS® with electrical properties (conductivity and permeability) of the tissues (fat, skin, and tumor). The detection of cancerous tumor (5 mm cube) at early stage was carried out for five different tumor positions (center, west, north, east, and south) inside the breast (XY plane). Furthermore, in each of the five different tumor positions, the tumor was located at 5 different depths (YZ or XZ plane) with the spacing of 10 mm. The simulation results obtained show that the sensor-antenna is fit for detect a 5 mm tumor. The tumor was detected in the 5 different positions (XY plane) and in the 5 different depths (XZ or YZ plane).